PENDEKATAN, METODE DAN PERAN FILSAFAT PENDIDIKAN - Sudianto; A., Marjuni; Andi Achruh (Pondok Pesantren Baitul Qur`an Sambas, 2024)
Regarding the philosophical approach to education, of course it contains many aspects and is verycomplex in nature. Because of its complex nature, there is no sufficient limit to explain the nature of education in its entirety. Limitations on the Philosophical Approach to Educational approaches made by experts vary, and their content sometimes differs from one another. These differences mayoccur because of differences in orientation, the basic concepts used, the analytical technique in writing this journal is thematic, where the results of the research show that there will be many benefits if you understand the philosophical foundation of education.